New technologies in the surgical treatment of wounds - Symulewicz, Michał; Korol, Filip; Edyko, Paweł; Jachowicz, Krzysztof; Dobek, Adam; Suwała, Zuzanna; Minkner, Mikołaj; Edyko, Krzysztof; Bieńkowski, Borys; Wójcik, Bartłomiej (Journal of Education, Health and Sport, 2023)
Introduction: Many wounds are treated surgically. For many years the method itself consisted mainly in cleaning the wounds and bringing its edges closer together, either by strips for closing the wounds or by suturing the wound with classic sutures or staples. Recently, new methods have emerged to support wound healing, which are discussed in this article. Materials and methods: The basis of the work were medical articles collected in the PubMed database. The research was conducted by analyzing key words such as: "surgical treatment of wounds", "new technologies in wounds", "wound healing and new technologies", "dressings in wound treatment", "new methods of accelerating wound healing". Results: In the process of surgical wound treatment the basis is still the closure and connection of the edges of the wounds, which prevents infections, accelerates healing and improves the cosmetic effect. However this is not the final stage of wound healing. Equally important is the subsequent appropriate selection of the dressing - appropriate in terms of its composition of active substances and absorption properties. The choice of the right dressing has a large impact on the final effect and the avoidance of infections or the subsequent appearance of the scar. Now we also have many new technologies to help heal wounds. They help not only to reduce the risk of infection, but also accelerate the healing process and shorten the treatment time.